2019
DOI: 10.1161/circulationaha.118.034731
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin-1 Assembles With Kv Channels to Govern Cardiomyocyte Repolarization and Contractility

Abstract: Background: Polycystin-1 (PC1) is a transmembrane protein originally identified in autosomal dominant polycystic kidney disease where it regulates the calcium-permeant cation channel polycystin-2. Autosomal dominant polycystic kidney disease patients develop renal failure, hypertension, left ventricular hypertrophy, and diastolic dysfunction, among other cardiovascular disorders. These individuals harbor PC1 loss-of-function mutations in their cardiomyocytes, but the functional consequences are unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 50 publications
1
32
0
2
Order By: Relevance
“…Several studies have reported cardioprotective effects of SERCA [ 66 ]. For example, cardiomyocyte repolarization and contractility are handled by SERCA in cardiomyocytes through the Kv channels [ 67 ]. Diabetes-induced cardiac remodeling and cardiomyopathy are also linked to dysregulated SERCA in a manner dependent on the miR-133a [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported cardioprotective effects of SERCA [ 66 ]. For example, cardiomyocyte repolarization and contractility are handled by SERCA in cardiomyocytes through the Kv channels [ 67 ]. Diabetes-induced cardiac remodeling and cardiomyopathy are also linked to dysregulated SERCA in a manner dependent on the miR-133a [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult cardiomyocytes were isolated from hearts of 8-16 weeks old male mice 57 . The isolated cells were plated in plating medium consisting of MEM, 2 mM L-glutamine, 1.26 mM CaCl 2 , 25 mM blebbistain, 1% penicillin/streptomycin, and 10% FBS.…”
Section: Controlmentioning
confidence: 99%
“…Notably, PC-1 is also involved in the pathogenesis of several cardiovascular diseases. The abated expression of PC-1 leads to the impaired contractility of cardiomyocytes via diminishing the calcium transients and sarcoplasmic reticulum calcium storage, consequently, resulting in cardiac dysfunction ( Balbo et al, 2016 ; Altamirano et al, 2019 ). Deficiency of PC-1 in endothelial cells also exhibited alterations in mechanosensitivity which further affected the flow-mediated vascular dilation ( Lorthioir et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%